The Relationship Between Knowledge and Parenting Patterns of Mothers and the Nutritional Status of Toddlers in the Working Area of the Patiluban Mudik Community Health Center, Natal District, 2022 - Batubara, Khoirunnisa'a (International Journal of Medicine And publich Health, 2024)
The results of a survey conducted in the working area of ​​the Patiluban Mudik Community Health Center show that mothers' parenting patterns are still said to be not good because in child care there are still many things that are not given enough attention, such as giving food to children, which does not place much importance on balanced food for children. Methods in research analytical survey methods with a cross sectional approach (Chi square with a sample size of 214 people. To obtain data in this study, researchers collected data through a questionnaire. With Chi square data analysis. The results of the discussion showed that the category of knowledge regarding toddler nutrition from all categories with sig (2 -tailed) 0.000 <0.000 it can be concluded that there is a relationship between mother's knowledge about toddler nutrition in the working area of ​​the Patiliban Mudik Community Health Center. Meanwhile, in the category of parenting patterns and toddler nutrition, the results of statistical processing using Asymp. Sig. (2-sided) Chi-square are 0.000. where 0.000 < 0.05 then Ha is accepted and Ho is rejected, so it can be concluded that there is a relationship between parenting patterns and the nutritional status of toddlers in the working area of ​​the Patiluban Mudik Community Health Center. Thus, it can be concluded that there is a relationship between knowledge and parenting patterns and the nutritional status of toddlers in the working area of ​​the Patiluban health center, Natal sub-district in 2022.